2018
DOI: 10.1186/s12904-018-0303-7
|View full text |Cite
|
Sign up to set email alerts
|

Palliative sedation in Germany: factors and treatment practices associated with different sedation rate estimates in palliative and hospice care services

Abstract: BackgroundClinical practice of Palliative Sedation (PS) varies between institutions worldwide and sometimes includes problematic practices. Little available research points at different definitions and frameworks which may contribute to uncertainty of healthcare professionals in the application of PS. This analysis investigates what demographic factors and characteristics of treatment practices differ between institutions with high versus low sedation rates estimates in Palliative and Hospice Care in Germany.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In a German study, Stiel et al attempted to review the factors associated with high versus low sedation rate estimates in Palliative and Hospice Care in Germany, and supported that even with the same clinical scenarios there would be variation in defining palliative sedation. They also concluded that there were no associations between health care professionals' demographic data and profession-related background and their reported palliative sedation rate in their practice (16). Some physicians suggested palliative sedation would have the 'Doctrine of Double Effect', which means that if doing something morally good has a morally bad side-effect, it is ethically acceptable to do it provided the bad side-effect was not intended.…”
Section: Discussionmentioning
confidence: 99%
“…In a German study, Stiel et al attempted to review the factors associated with high versus low sedation rate estimates in Palliative and Hospice Care in Germany, and supported that even with the same clinical scenarios there would be variation in defining palliative sedation. They also concluded that there were no associations between health care professionals' demographic data and profession-related background and their reported palliative sedation rate in their practice (16). Some physicians suggested palliative sedation would have the 'Doctrine of Double Effect', which means that if doing something morally good has a morally bad side-effect, it is ethically acceptable to do it provided the bad side-effect was not intended.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with case vignettes in Germany demonstrated considerable differences in the intuitive attribution of the most commonly used term “palliative sedation.” 12 A retrospective chart review revealed “no consistent pattern regarding labelling.” 13 A qualitative study indicated that the term “palliative sedation” is used inconsistently and sometimes misinterpreted as deep continuous sedation. 14 This might impede decision making and transparent communication with patients and within care teams.…”
Section: Introductionmentioning
confidence: 99%
“…Experts within and outside palliative care criticize the terminological situation concerning sedation in palliative care and have repeatedly requested improvement. 1 , 2 Definitions differ significantly in content and structure, 3 and there is uncertainty among practitioners about identifying cases with commonly used terms such as “palliative sedation.” 4–6 …”
Section: Introductionmentioning
confidence: 99%